Idiopathic gingival enlargement and its management - Shetty Arvind; Shah Hardik; Patil Mallika; Jhota Komal (Wolters Kluwer Medknow Publications, 2010)
Idiopathic gingival enlargement is a proliferative fibrous lesion of the gingival tissue that causes esthetic and functional problems. Both genetically and pharmacologically induced forms of gingival enlargement exist. This case report addresses the diagnosis and treatment of a case of idiopathic gingival enlargement in a 13-year-old female. The patient presented with generalized diffuse gingival enlargement involving the maxillary and mandibular arches extending on buccal and lingual/palatal surfaces and covering incisal / occlusal third of the tooth resulting in difficulty in speech and mastication since last three years. Patient also gave a history of surgical treatment being carried out four years back in upper anterior region suggesting of recurrence. Biopsy report confirmed the diagnosis of gingival hyperplasia. Gingivectomy was carried out in all four quadrants by using four different methods.